African Americans in Indianapolis : The Story of a People Determined to Be Free - Williams, David Leander (Book collections on Project MUSE., 2022)
African Americans in Indianapolis serves as a reminder of the advancements that our midwestern ancestors made toward freedom and equality, as well as the continual struggle against inequalities that must be overcome.